2003
DOI: 10.1021/jo026867s
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Molecular Absolute Configuration through the ab Initio Hartree−Fock Calculation of the Optical Rotation:  Can the Circular Dichroism Data Help in Reducing Basis Set Requirements?

Abstract: In this paper the calculation of the optical rotation (OR) of some rigid organic molecules, using the Hartree-Fock method with small (6-31G, DZP) basis sets, has been studied thoroughly to carefully evaluate the scope and limitations of this method, previously introduced by other authors. Calculations on test molecules (compounds 1-13) together with a careful analysis of their CD spectra allow a simple criterion for the reliability of this approach to be formulated: for unsaturated and/or aromatic (i.e., absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…The enantiomer ()-11ca was then used in one of their further reports [70], and its absolute configuration is not unambiguously depicted in [71]. Astonishingly, and without other explanation than quoting the reference of the racemic material [43], they later claimed that the antipode (À)-11ca is responsible for the sandalwood scent [72] and finally used this latter compound for further studies [73] [80]. The independent synthesis and olfactive evaluations of both pure enantiomers of 17ca,cb and 11ca,cb by asymmetric deprotonation [81] will be reported elsewhere by Dr. C. Margot.…”
Section: Shown By Comparison Of (à)-(Rz)-10a/()-(re)-10a and ()-(Z)mentioning
confidence: 99%
“…The enantiomer ()-11ca was then used in one of their further reports [70], and its absolute configuration is not unambiguously depicted in [71]. Astonishingly, and without other explanation than quoting the reference of the racemic material [43], they later claimed that the antipode (À)-11ca is responsible for the sandalwood scent [72] and finally used this latter compound for further studies [73] [80]. The independent synthesis and olfactive evaluations of both pure enantiomers of 17ca,cb and 11ca,cb by asymmetric deprotonation [81] will be reported elsewhere by Dr. C. Margot.…”
Section: Shown By Comparison Of (à)-(Rz)-10a/()-(re)-10a and ()-(Z)mentioning
confidence: 99%
“…The implementation of (frequency-dependent) linear response theory-specifically for the calculation of the chiroptical tensors-at various levels of theory, from Hartree-Fock 8,9 to Density Functional Theory (DFT) [10][11][12][13][14][15] and coupled cluster (CC) methods, 14,16,17,18 often together with the use of London atomic orbitals (LAOs) 19 to remove unphysical origin dependencies in the magnetic-field dependent quantities, has allowed the accurate (and reliable) determination of the rotatory power for a large number of molecular systems. [20][21][22][23][24] Several studies, in particular on rigid molecules, have shown that values of specific rotations as accurate as 63 deg cm 2 g À1 can be obtained if the molecular geometry is optimized at the DFT/Becke-3-parameter-Lee-Yang-Parr (B3LYP) 25 (DFT/B3LYP) level using a basis set of (at least) 6-31G** quality, and the ORs are determined using time-dependent (TD)-DFT/B3LYP and a basis set of (at least) aug-cc-pVDZ quality. 11,24,26,27 Complications might arise when the systems under investigation are ''flexible''-that is, they exist in more than one stable conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] We had already published in the past some NIR-VCD data for 1 and 2 and for some related compounds. 13,14 However, we have recently improved our apparatus for measuring NIR-VCD, obtaining better VCD data in the overtone region at ∆V ) 3, new VCD data at ∆V ) 4 for fenchone, and VCD data in the yet unexplored regions of CH-stretchings/HCH-bendings combinations.…”
Section: Introductionmentioning
confidence: 99%